Cardiovascular magnetic resonance measurement of myocardial extracellular volume in health and disease. Issue 19 (30th August 2012) - Sado, Daniel M; Flett, Andrew S; Banypersad, Sanjay M; White, Steven K; Maestrini, Viviana; Quarta, Giovanni; Lachmann, Robin H; Murphy, Elaine; Mehta, Atul; Hughes, Derralynn A; McKenna, William J; Taylor, Andrew M; et al.
Abstract : Objective: To measure and assess the significance of myocardial extracellular volume (ECV), determined non-invasively by equilibrium contrast cardiovascular magnetic resonance, as a clinical biomarker in health and a number of cardiac diseases of varying pathophysiology. Design: Prospective study. Setting: Tertiary referral cardiology centre in London, UK. Patients: 192 patients were mainly recruited from specialist clinics. We studied patients with Anderson–Fabry disease (AFD, n=17), dilated cardiomyopathy (DCM, n=31), hypertrophic cardiomyopathy (HCM, n=31), severe aortic stenosis (AS, n=66), cardiac AL amyloidosis (n=27) and myocardial infarction (MI, n=20). The results were compared with those for 81 normal subjects. Results: In normal subjects, ECV (mean (95% CI), measured in the septum) was slightly higher in women than men (0.273 (0.264 to 0.282 vs 0.233 (0.225 to 0.244), p<0.001), with no change with age. In disease, the ECV of AFD was the same as in normal subjects but higher in all other diseases (p<0.001). Mean ECV was the same in DCM, HCM and AS (0.280, 0.291, 0.276 respectively), but higher in cardiac AL amyloidosis and higher again in MI (0.466 and 0.585 respectively, each p<0.001). Where ECV was elevated, correlations were found with indexed left ventricular mass, end systolic volume, ejection fraction and left atrial area in apparent disease-specific patterns. Conclusions: Myocardial ECV, assessed non-invasively in the septum with equilibrium contrast cardiovascular magnetic resonance, shows gender differences in normal individuals and disease-specific variability. Therefore, ECV shows early potential to be a useful biomarker in health and disease.